2014
DOI: 10.5624/isd.2014.44.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Clival lesion incidentally discovered on cone-beam computed tomography: A case report and review of the literature

Abstract: An osteolytic lesion with a small central area of mineralization and sclerotic borders was discovered incidentally in the clivus on the cone-beam computed tomography (CBCT) of a 27-year-old male patient. This benign appearance indicated a primary differential diagnosis of non-aggressive lesions such as fibro-osseous lesions and arrested pneumatization. Further, on magnetic resonance imaging (MRI), the lesion showed a homogenously low T1 signal intensity with mild internal enhancement after post-gadolinium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…facial and skull base CMF). [10][11][12][13][14][15][16][17][18][19][20] Our goal was to analyse the histopathologically proven CMF cases in University Hospital Leuven, focusing on imaging landmarks which can help us in the diagnostic work-up and to compare these with the published literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…facial and skull base CMF). [10][11][12][13][14][15][16][17][18][19][20] Our goal was to analyse the histopathologically proven CMF cases in University Hospital Leuven, focusing on imaging landmarks which can help us in the diagnostic work-up and to compare these with the published literature.…”
Section: Discussionmentioning
confidence: 99%
“…In older patients, lesions are more frequently seen at rare localizations. [16][17][18][19][20][21][22][23] In our study group, three patients were diagnosed in the fifth and one patient in the sixth decade of life. However, these lesions did not appear in atypical localizations.…”
Section: Discussionmentioning
confidence: 99%
“…The concretions have been associated with halitosis and tonsillar abscess [43]. An elongated stylohyoid complex has been associated with symptoms caused by compression of nerves, compression of carotid artery or tendinitis, such as cervicofacial and throat pain, or dysphagia [44].…”
Section: Discussionmentioning
confidence: 99%
“…It generally manifests itself in the basisphenoid bone and pterygoid process region, 3,4 with the petrous temporal apex and clivus also being reported areas. 5,6 In fact, accessory pneumatization areas such as the occipital and frontal bones, as well as the maxillary bone, have also been defined. 3,4 However, in the ethmoid bone, arrested pneumatization has not been defined, likely due to its aeration mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Arrested pneumatization has generally been defined as an incidental imaging finding. 3,6 De Jong et al reported in a case presentation that for several years their patient suffered headache, photophobia, intermittent nausea, and vomiting, but no characteristic feature was identified from physical, neurologic, and laboratory findings. 5 In our cases also, arrested pneumatization was incidentally identified at diag-nostic imaging examination for various disease entities.…”
Section: Discussionmentioning
confidence: 99%